2021
DOI: 10.18178/ijmlc.2021.11.4.1055
|View full text |Cite
|
Sign up to set email alerts
|

Black Sigatoka Classification Using Convolutional Neural Networks

Abstract: In this paper we present a methodology for the automatic recognition of black Sigatoka in commercial banana crops. This method uses a LeNet convolutional neural network to detect the progress of infection by the disease in different regions of a leaf image; using this information, we trained a decision tree in order to classify the level of infection severity. The methodology was validated with an annotated database, which was built in the process of this work and which can be compared with other state-of-the-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…The proposed model has achieved an accuracy of 94%. Cristian et al [19] have identified the progress of disease infection in banana leaf images using the LesNet deep learning model and the intensity of the diseases is measured using a Decision Tree (DT).…”
Section: Identification and Prediction Of Diseases In Banana Plantsmentioning
confidence: 99%
“…The proposed model has achieved an accuracy of 94%. Cristian et al [19] have identified the progress of disease infection in banana leaf images using the LesNet deep learning model and the intensity of the diseases is measured using a Decision Tree (DT).…”
Section: Identification and Prediction Of Diseases In Banana Plantsmentioning
confidence: 99%